Criminal Acts of Persecution That Resulted in The Death of The Victim - Ruth Febriani Hia; Ojak Nainggolan (Warmadewa Press, 2025)
This study discusses the criminal act of assault that resulted in death, focusing on the case study of Decision Number 467/Pid.B/2022/PN Stb. The purpose of this research is to explore the importance of applying the principle of